Environmental component of product life cycle assessment - Комариста, Богдана Миколаївна (Technology audit and production reserves, 2013)
The methods of environmental assessment of products were analyzed in the paper. The basic stages of the product life cycle assessment were given. The index method was proposed to assess the ecological impact of the product on the environment throughout its life cycle. The index method involves obtaining the estimates in the form of dimensionless parameters by simplified mathematical dependences for easy implementation and use of these estimates by relevant regulatory authorities and provision of product information to the consumer. According to the algorithm it is proposed to evaluate the impact of the product throughout its life cycle on the environment using four index indicators, namely the unitary index of surface waters pollution, unitary index of air pollution, unitary index of soil pollution and unitary index of waste formation. Based on these indexes, the unitary index of effects on the environment is formed, which allows making conclusions on the adverse impact of the product on the environment during all stages of its life cycle.